PENINGKATAN SIKAP MATEMATIKA MENGGUNAKAN METODE PEMBELAJARAN KOOPERATIF TIPE STAD - Rahayu S, Putri (Institut Daarul Qur'an Jakarta, Indonesia, 2022)
This study aims to improve students' attitudes towards mathematics by applying the Student Team Achievement Division (STAD) type of cooperative learning to fourth grade students. This research is a Classroom Action Research (CAR) conducted in a participatory collaborative manner between mathematics teachers and researchers at SDN 1 Rejo Basuki. The research subjects were fourth grade students. Based on the results of the questionnaire in cycles I and II, there was an increase in students' attitudes towards mathematics. In the first cycle the average attitude of students has not reached the predetermined target. Improvements were made in cycle II by the teacher observing the learning steps. Learning with STAD can improve attitudes towards mathematics. This is marked by an increase in students' attitudes towards mathematics from a scale of 0-150 in the initial conditions of 88.03 with low criteria, increasing to 107.23 with high criteria in the first cycle, and continuing to increase to 109.87 with high criteria in the second cycle, student mastery in cognitive aspects increased. The score in the pretest was 0%, in the first cycle it became 33.33% and the second cycle became 56.67%. The implementation of learning with the STAD type of cooperative learning method went well, it can be seen from the results of learning observations where the achievement of the learning process in the initial conditions was only 40%, there was an increase in the first cycle of 84.17%, and an increase again in the second cycle of 96.11% .